Caste System in Medieval Nepal - Kafle, Dol Raj (Tribhuvan University Journal, 2021)
This article attempts to explore the functioning and dynamics of the caste system that prevailed in medieval Nepal from 879 to 1768 AD. Nepal is a country which has a rich diversity of castes, languages, religions, and cultures. On the one hand, it has long been a matter of pride for Nepal to host such a diverse society and on the other hand, this very diversity has espoused various critical interpretations, particularly when it comes to ethnicity and power relations. While the ancient traditions and culture of the country continue to shape the foundation of the present Nepali society, the influence of the medieval social and caste system is still present today. Irrespective of the socioeconomic implications of the caste system in the Nepali society, what the society practiced in medieval times in terms of different cases has a strong influence on the way Nepali society functions today. Although it cannot be said that the caste system is necessary and useful in all societies, there is evidence that the system was introduced by the kings and subjects of that time to make the medieval Nepali society systematic and dignified in their own ways. Of course, society is always fluid and should continue to change. However, the fact that the medieval caste system continues to survive in today’s Nepal. It is a strong proof that great change has not taken place yet in our society. The medieval caste system is becoming the basis of human identity even today. The co-existence of a diverse group of people in Nepali society has in both way nurtured the caste system by promoting the idea that diversity is good for society and its functioning. While there has been an effect of melting pot concept owing to urbanization and population growth in recent years, the fabric of Nepali society in the medieval period demonstrates a distinct caste system brought to operation from a utilitarian motive. This article aims to analyse this very distinct feature of Nepal’s medieval society wrought in the caste system in its crude form. The article not just explores the functioning of the caste system in medieval Nepali society but also exposes how it remains intact even today. This article uses descriptive and analytical methods. In course of writing, the arguments have been made based on secondary resources.